2022
DOI: 10.3389/fpsyg.2022.913773
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transformational leadership dimensions on employee performance in the hospitality industry in Malaysia

Abstract: Employee performance plays a crucial role in the productivity of organizations, especially in the hospitality industry in Malaysia. This work performance is influenced by leadership style, and finding the type of leadership style that is suitable to apply to employees is crucial, especially in the midst of the COVID-19 pandemic. Transformational leadership theory is selected for this study in determining leadership styles. There are four dimensions under transformational leadership theory, namely idealized inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Consistent with the results of Chen’s, Sangperm’s, Lieber’s, and Teoh’s studies that positive traits of self-expectation leadership were positively associated with organizational commitment and HHB ( Chen, 2011 ; Lieber et al, 2014 ; Sangperm, 2017 ; Teoh et al, 2022 ), our study demonstrated the same results in the field of HAI prevention and control. Research from the field of psychology explained the possible reason for the results that medical staff with high positive traits of self-expectation leadership were more active and committed in the organization and displayed creativity and initiative in their work behavior ( DiLiello and Houghton, 2006 ).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the results of Chen’s, Sangperm’s, Lieber’s, and Teoh’s studies that positive traits of self-expectation leadership were positively associated with organizational commitment and HHB ( Chen, 2011 ; Lieber et al, 2014 ; Sangperm, 2017 ; Teoh et al, 2022 ), our study demonstrated the same results in the field of HAI prevention and control. Research from the field of psychology explained the possible reason for the results that medical staff with high positive traits of self-expectation leadership were more active and committed in the organization and displayed creativity and initiative in their work behavior ( DiLiello and Houghton, 2006 ).…”
Section: Discussionsupporting
confidence: 91%
“…Qingjin et al (2010) also found that a loose, harmonious, free, open and inclusive scientific research environment is conducive to improving the output of innovative achievements. Teoh et al (2022) point out that idealized influence and inspirational motivation, have a significant positive influence on employee performance.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Leaders and employees are two categories of "people" in a company. As a result, research on leaders and employees has always been a theoretical topic of great interest in the field of management as it is related to an organization's success or failure (Teoh et al, 2022;Wang, Lin, Osman, Farooq, & Raju, 2021). Employee achievement in the FMCG sector is typically connected with sales performance and employees in this area experience greater marketing influence than those in other industries.…”
Section: Introductionmentioning
confidence: 99%